Double-poling physiology and kinematics of elite cross-country skiers: Specialized long-distance versus all-Round skiers - Skattebo, Ø.; Losnegard, T.; Stadheim, H. K. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Long-distance cross-country skiers specialize to compete in races >50 km predominantly using double poling (DP). This emphasizes the need for highly developed upper-body endurance capacities and an efficient DP technique. The aim of this study was to investigate potential effects of specialization by comparing physiological capacities and kinematics in DP between long-distance skiers and skiers competing using both techniques (skating/classic) in several competition formats ("all-round skiers"). Methods: Seven male long-distance (32 [6] y, 183 [6] cm, 76 [5] kg) and 6 all-round (25 [3] y, 181 [5] cm, 75 [6] kg) skiers at high international levels conducted submaximal workloads and an incremental test to exhaustion for determination of peak oxygen uptake (VO2peak) and time to exhaustion (TTE) in DP and running. Results: In DP and running maximal tests, TTE showed no difference between groups. However, long-distance skiers had 5-6% lower VO2peak in running (81 [5] vs 85 [3] mL/kg·min; P = .07) and DP (73 [3] vs 78 [3] mL/kg·min; P < .01) than all-round skiers. In DP, long-distance skiers displayed lower submaximal O2 cost than all-round skiers (3.8 ± 3.6%; P < .05) without any major differences in cycle times or cyclic patterns of joint angles and center of mass. Lactate concentration over a wide range of speeds (45-85% of VO2peak) did not differ between groups, even though each workload corresponded to a slightly higher percentage of VO2peak for long-distance skiers (effect size: 0.30-0.68). Conclusions: The long-distance skiers displayed lower VO2peak but compensated with lower O2 cost to perform equally with the all-round skiers on a short TTE test in DP. Furthermore, similar submaximal lactate concentration and reduced O2 cost could be beneficial in sustaining high skiing speeds in long-duration competitions..